Surgical and percutaneous pulmonary valve replacement in England over the past two decades - Larsen, Signe H; Dimopoulos, Konstantinos; Gatzoulis, Michael A; Uebing, Anselm; Shore, Darryl F; Alonso-Gonzalez, Rafael; Kempny, Aleksander (Heart (British Cardiac Society), 2019)
ObjectivePulmonary valve replacement (PVR) is often required in patients with congenital heart disease. We aimed to describe temporal trends in PVR in a nationwide English cohort between 1997 and 2014, survival and the need for re-PVR.MethodsPatients were identified in the Hospital Episode Statistics Database. Survival data were retrieved from the UK Office for National Statistics.ResultsA total of 2733 patients underwent PVR (2845 procedures) over the study period. Median age at first procedure increased from 20.1 years in 1997–2005 to 24.7 years in 2006–2014. The annual number of PVRs increased from 23 in 1997 to 251 in 2014. Homografts were the most common choice in the early years, but the use of xenografts increased after 2005. During a median follow-up of 5.8 years, 176 patients died and 108 required redo PVR. Early (30 day) survival was 98% for all PVRs and was similar for all types of prostheses but longer-term mortality dropped to 92% at 10 years and 90% at 15 years. Age >16 years and percutaneous PVR were risk factors for death. The cumulative incidence for re-PVR at 10 years was 8% for all PVRs and 11% at 15 years. Risk factors for re-PVR were complex diagnosis, male gender and black ethnicity.ConclusionThere was a significant increase in the number of PVRs performed in England over the last two decades and a significant change in the type of prosthesis employed. While early mortality was low across the board, longer-term mortality was not negligible in this young population.